The Role of the State in Canadian Labour Relations. - Sack, Jeffrey; Lee, Tanya (Relations industrielles / Industrial Relations, 1989)
The authors examine the role of the State in industrial relationsin Canada. They address themselves particularly to the questionsin which circumstances and to what extent the State shouldintervene.